Tarikh Falsafah al-Lughah al-Insaniyah - Ningsih, Wiwik Prasetiyo (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar, Pamekasan, 2024)
There are many differences in the discussion of the origin of language. The results of studies on this issue have not been conclusive due to the difficulty researchers face in reaching a consensus. So, what is the history of the origin of language in this world? There are many theories about the origin of language to answer this problem. The aim of this research is to uncover the history of the emergence of language. The approach of this research is qualitative. The researcher used the library method for her research. She collected data through documentation, which involved reading books, articles, and research related to this topic. The data analysis method used in this research is content analysis. The results of this research are that the researcher found various theories about the origin of language, including the divine theory, the convention theory, the Bow-wow theory (theory of natural sound imitation), the Pooh-pooh theory (theory of emotional exclamations), the Yo-he-ho theory (theory of vocal responses to muscular movements), and the like. None of these theories are entirely right or wrong, but language encompasses all of them.